(untitled) (Studia austriaca, 2015)
The sixteenth-century migrations of Anabaptist communities within Europe, particularly Tyrol, becomes an important literary theme for the Austrian novelist Maria Veronika Rubatscher who draws parallels between the relocated fellowship and the German-speaking minority in Italy after the dissolution of the Austro-Hungarian Empire. Discussing the portrait of Tyrolean Anabaptism in her novel Das Lutherische Joggele, this paper shows how the author utilizes the movement’s history as a means of expressing her nationalistic identity.